Pengaruh komitmen organisasi dan budaya organisasi terhadap kinerja Organisasi Perangkat Daerah Kota Tidore Kepulauan - Dahlan, Fadli; Madjodjo, Farid (Indonesia Accounting Journal, 2020)
The implementation of local government performance accountability is an accountability that begins from the planning, preparation, and implementation of the government's duties and functions in realizing the vision, mission, and objectives that have been set so that they can be accounted for to the public. This study aims to analyze and understand the influence of organizational commitment and organizational culture on the performance of Regional Instrument Work Unit of Local Government (or called OPD) of the City of Tidore Islands. This study will explain the relationship between several variables through hypothesis testing or explanatory research. The population for this study is 32 OPD which gives 160 respondents as the sample after applies the probability sampling. The result of multiple linear regressions shows that the organizational commitment has positive and significant effect on the OPD’s performance which means that with organizational commitment then the employees of OPD are able to give positive contributions to the OPD’s performance. This study also finds that the organizational culture has positive and significant effect on the OPD’s performance which means that the organizational culture has the ability to improve the OPD’s performance.